(untitled) (Scientific Conference on Multidisciplinary Studies, 2025)
This scientific thesis is dedicated to studying the developmental stages and modern trends in the pharmaceutical industry. The article analyzes recent technological advancements, international standards, and their significance in clinical settings, particularly in pediatrics and neonatology. It also explores innovations in drug manufacturing processes, the prospects of personalized medicine, and sustainability principles that shape the future of the modern pharmaceutical sector.